Assessment of the Impact of the Crisis on New PPI Projects : Update Five - World Bank (Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation (Private Participation in Infrastructure (PPI) projects) reaching closure in developing countries grew by 22 percent in the third quarter of 2009, and by 10 percent in the first three quarters of the year, compared with the same periods of 2008. These growth rates indicate a strong recovery from the 54 percent decline in the second half of 2008 compared with the same period of 2007. But investment grew selectively, concentrated in large energy projects in a few countries: Brazil, India, and Turkey. The Russian Federation, by contrast, saw a sharp decline in investment as a result of the global financial crisis and the end of the RAO UES privatization program. If these four countries were excluded, investment in developing countries would have fallen by 49 percent in the third quarter of 2009, and by 5 percent in the first three quarters, compared with the same periods of 2008. Among sectors, energy was the only one with investment growth in 2009, thanks to activity in greenfield power plants. Across sectors, large projects (US$500 million or more) accounted for the investment growth. Private activity as measured by number of projects remained slower than before the full onset of the financial crisis. The number of projects reaching closure was 27 percent lower in the third quarter of 2009, and 10 percent lower in the first three quarters, than in the same periods of 2008. These trends suggest greater project selectivity. Indeed, the large projects that are reaching closure are characterized by strong economic and financial fundamentals and the backing of financially solid sponsors and governments.